Two taxa of the genus Epipactis Zinn (Orchidaceae) new for the flora of Ukraine - Kreutz, C.A.J.; Fateryga, A.V. (Український ботанічний журнал, 2012)
Epipactis turcica Kreutz and E. helleborine subsp. orbicularis (C. Richt) E. Klein. are reported from the Crimea as new for the flora of Ukraine. Data on key diagnostic characters of the taxa and collected herbarium specimens are provided.